A HISTORICAL STUDY ON LATIN ROMAN CATHOLIC COMMUNITY OF KANYAKUMARI REGION - Jainrose. M; Dr. R. Ramasubramanian (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research explores the historical development and socio-cultural contributions of the Latin Roman Catholic community in the Kanyakumari region, situated at the southern tip of India. The Latin Catholic presence in this region traces back to the Portuguese colonial period, with the establishment of churches, schools, and social institutions that significantly shaped the local landscape. The study delves into the community’s origins, highlighting the influence of colonial missionaries and their efforts in converting and integrating the local population into the global Catholic network. The article further examines the challenges faced by the community, including the impact of British colonial rule, the post-independence socio-political shifts, and the evolving religious practices within the context of a predominantly Hindu region. Through archival research, oral histories, and the analysis of church records, the study aims to uncover the unique identity of the Latin Roman Catholics of Kanyakumari, focusing on their religious, educational, and economic transformations. This research also investigates the community’s role in fostering inter-religious dialogues and its ongoing relevance in the modern socio-political fabric of the region. Ultimately, the paper offers a comprehensive understanding of the Latin Roman Catholic community’s contributions to the religious and cultural diversity of Kanyakumari